1999
DOI: 10.1177/014556139907800820
|View full text |Cite
|
Sign up to set email alerts
|

Subglottic Carcinoma: Review of a Series and Characterization of its Patterns of Spread

Abstract: The rarity of primary subg lottic malignan cies, along with the varied definitions of the anat omi c confines of this region, have lim ited our und erstanding ofthe pa tte rns of tum or spread within the subglottis. We conducted a retrospective chart review to analyze clinical and pathologic data in pa tients with subglottic carcinoma. A patt ern of disease progressi on was ident ified, whic h is defin ed by the cartilaginous laryngealfra mework, with thefib roelastic barriers susceptible to tumor invasion. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 9 publications
2
50
0
Order By: Relevance
“…The bulk of invasive carcinoma was found to penetrate through gaps between tracheal rings, respecting the boundaries of the cartilaginous framework. The majority of spread was found to be through the paraglottic space into the region bounded medially by the conus elasticus and laterally by the laryngeal cartilages …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of invasive carcinoma was found to penetrate through gaps between tracheal rings, respecting the boundaries of the cartilaginous framework. The majority of spread was found to be through the paraglottic space into the region bounded medially by the conus elasticus and laterally by the laryngeal cartilages …”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that subglottic tumors frequently involve the paraglottic space, increasing likelihood of extra laryngeal spread . Brennan et.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach to advanced SCCA of the subglottic larynx is to initially secure the airway and to accurately stage the lesion. Staging can be difficult (our own studies demonstrate that seemingly early tumors can escape into the neck through the intercartilagenous tracheal spaces) [33]. In this setting, cartilage invasion might not be demonstrated on CT. After staging, these patients are generally offered an organ preservation approach.…”
Section: Treatment Of Subglottic Larynxmentioning
confidence: 95%
“…Similarly, tumors were enabled to spread into the paraglottic space, in the region bounded medially by the conus elasticus and laterally by the laryngeal cartilages. 30 Furthermore, lymphatic drainage of the anterior subglottis traverses the cricothyroid membrane to reach pretracheal and prelaryngeal nodes. Posterolaterally, lymphatic drainage occurs through the cricotracheal membrane to paratracheal nodes.…”
Section: Anatomic Basismentioning
confidence: 99%